Embedded plasmonic nanostructures: synthesis, fundamental aspects and their surface enhanced Raman scattering applications. Issue 3 (2nd July 2016) - Prakash, Jai; Harris, R.A.; Swart, H.C.
Abstract : The unique physical and tunable optical properties of noble metal nanoparticles (NPs) provides the opportunity to develop new sensing platforms with enhanced capabilities in the specific detection of a variety of small molecules. While noble metal NPs are interesting as nanomaterials, future and practical applications as high-performance novel functional materials will require the use of these NPs embedded in suitable host materials. This review details how embedded noble metal NPs and the local environment influence the sensing properties for potential application in nano-biotechnology, ultrasensitive chemical and biochemical detection by surface enhanced Raman scattering (SERS) nanotechnology. Although the synthesis and potential applications of noble metal NPs based SERS substrates have been reviewed previously, there is a growing interest in synthesis and functionalisation of embedded noble metal NPs and their applications as SERS substrates. This topic has been rarely reviewed in literature. In particular, we review the highly active solid and thin film SERS substrates such as polymer and glass substrates embedded with noble metal NPs. We also discuss their optical properties due to the localised surface plasmon resonance and enhanced local electromagnetic field which are responsible for enhanced SERS activity with emphasis on their fundamental and technological applications. This review also includes a new class of promising porous coordination polymeric SERS substrates (a metal-organic framework) embedded with noble metal NPs. The review first explains many fundamental key concepts of SPR and SERS enhancement as well as factors affecting these properties in the case of embedded NPs. This then summarises methods for the fabrication of highly reproducible and robust SERS substrates embedded with NPs followed by their SERS application in detection of several chemical and biological molecules. The article also describes the recent developments in the fabrication of these SERS substrates embedded with noble metal NPs from conventional chemical routes to physical methods including novel ion beam techniques.